Mortgage Financing: Access, Knowledge, Attitudes and Challenges Experienced by Urban Housing developers - Nakiwala, Margaret; Mukiibi, Stephen; Kigundu, Amin Tamale (East African Nature and Science Organization, 2023)
This paper summarises the housing challenges that stem from the increasing population growth in Uganda by reviewing the literature. The housing deficit is the problem that the goals set in the National Development Plan (NDP III) determine to alleviate. In her NDP III, Housing Finance Bank strategised to offer affordable mortgages to Ugandan citizens. It is clearly stated in the NDP III that the problem of housing financing is left to the individuals as the central government cannot set up housing for all its citizens. The theories that guide the use of mortgage financing include the Lien, Title, Intermediate, and Lifestyle theories. This argument is presented in a systematic literature review of studies about the issues around mortgage financing in different parts of the world—specifically, Access. Established Knowledge, Attitudes and Challenges of accessing mortgage financing were issues of concern that needed researching.
Moreover, the literature confirmed that the biggest challenge that housing developers endure to access mortgage financing is the high-interest rates, especially in developing countries. Various economies have people with different knowledge about Mortgage Financing. Uganda is the case study that aimed at increasing urban housing accessibility by citizens of the country. The research method applied in this paper is purely qualitative research that analyses the opinions of different academic scholars in mortgage financing. However, this paper argues that financial institutions' eligibility terms significantly limit Access to Urban Housing through mortgage financing. The set terms need to reviewing to suit the informal setting of developing countries like Uganda. The recommendation from the study is the adoption of a central tool to oversee the set eligibility terms on mortgages.